Identifikasi Risiko Program Maintenance dalam Pengelolaan Proyek Berbasis Agile Menggunakan Pohon Klasifikasi - Billyanto Hendrik; Bernard Renaldy Suteja (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Agile is a system development life cycle methodology that focuses on development interactions that involve the user with the development team led by the project manager as an intermediary between the client and the development team, with the project manager as the project leader, it is expected that this role can carry out project planning by making estimates and designing. project. The worst thing that can happen if the application fails to meet client expectations is the additional development time called maintenance, this risk will create losses to the company even though maintenance is an additional service, but this risk tends to be negative because it can have a negative impact on the company and members of the development team. responsible for the project, the project manager must be able to identify risks earlier during the sprint, so in this study we will discuss the analysis and risk identification of maintenance programs in agile-based project management, as a research analyst method will use a classification tree to group them so that It can be found at the sprint stage how much risk has started to be made, so that the project manager can make corrections at the next sprint to reduce maintenance risk